The Role of Leadership in Fostering Psychological Safety in Healthcare: Protocol for a Systematic Review of Qualitative Studies - Ravi Shankar; Fiona Devi; Amartya Mukhopadhyay (International Journal of Qualitative Methods)
Psychological safety, a shared belief held by members of a team that the team is safe for interpersonal risk-taking, is a critical factor in healthcare team performance and patient safety. Leadership plays a crucial role in creating psychologically safe environments that encourage open communication, problem-solving, and innovation. This qualitative evidence synthesis aims to synthesize the evidence on the role of leadership in fostering psychological safety in healthcare settings. The synthesis will follow the Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ) guidelines and will include qualitative studies that explore leadership behaviors, strategies, and interventions that promote psychological safety in healthcare teams. The synthesis will search multiple electronic databases (PubMed, Web of Science, Embase, CINAHL, MEDLINE, The Cochrane Library, PsycINFO, and Scopus) from inception to December 2024. Two reviewers will independently screen and select studies, extract data, assess methodological quality using the Critical Appraisal Skills Programme (CASP) Qualitative Checklist, and assess confidence in the findings using the Grading of Recommendations Assessment, Development, and Evaluation - Confidence in the Evidence from Reviews of Qualitative research (GRADE-CERQual) approach. A thematic synthesis will be conducted to identify key themes related to leadership behaviors, strategies, and interventions that promote psychological safety. This synthesis will provide valuable insights into the role of leadership in creating psychologically safe environments and inform the development of evidence-based leadership interventions to enhance healthcare team performance and patient safety.